Социология управления: поиск ответов на вызов времени - Нагорный, Б. (Социология: теория, методы, маркетинг, 2001)
The article investigates the problems of new management paradigm creation under conditions of transforming society. Management sociology must give a well-reasoned answer to the challenge of time taking into consideration the appearance of new subjects and objects of management, factors of globalization and new managerial relations.